Kinerja Keuangan Daerah Kabupaten Sarolangun Sebelum Dan Selama Covid-19 - Riszki, Riszki; Yudi, Yudi; Kusumastuti, Ratih (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This research aims to see how the performance of Sarolangun Regency was carried out during the emergence of the Covid 19 pandemic.  This research belongs to a quantitative descriptive type with a comparative concept with the Paired Sample T-Test on APBD with analysis of the ratio of fiscal decentralization, regional financial independence, and the effectiveness and efficiency of PAD.  In the analysis used, it shows the results of a very poor ability to implement decentralization, lack of independence in carrying out financial performance which is still in an instructive relationship pattern, and the effectiveness of PAD which is ineffective because it fluctuates and tends to decrease, and the efficiency of PAD which included in the criteria of inefficiency.  The conclusions that can be drawn from the results of testing the variables do not show any significant differences in fiscal decentralization, regional financial independence, and PAD efficiency, except for the PAD effectiveness variable has significant differences.  However, overall the financial performance of Sarolangun Regency did not experience any difference either before or during the Covid-19 outbreak.